(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Due to the anatomy of the heart and blood vessels, depending on which wall of the coronary artery supplies blood to the myocardium, when damage occurs due to impaired nutrition and oxygen metabolism in this area, damage occurs to the conduction and excitatory system in this area. is damaged and various arrhythmias are observed in the clinic.